Stress-strain state of metal-wood crossbar of double-hinged frames - A. I. Bulgakov; M. H. Kalieva; M. O. Konusov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective the purpose of these studies is to choose the optimal design solution in the design of double-hinged wooden frames with a metal-wood crossbar, based on a comparative analysis of the stress-strain state of a metal-wood crossbar in the form of beams of various shapes, determined by the results of theoretical studies and numerical experiment.Method. Determination of the stress-strain state of metal-wood beams using theoretical studies and numerical experiment performed in the computer complex PC "LIRA".Result. Optimal design solutions of metal-wood crossbars of double-hinged frames in the form of reinforced beams of various shapes are proposed.Conclusion. The bearing capacity of double-hinged frames with a crossbar in the form of reinforced glued wood beams is on average 35 - 38% higher than the load bearing capacity with a crossbar in the form of unreinforced glued wood beams.The use of metal-wood (reinforced) beams makes it possible to optimize the cross-section by reducing the cross-section height, thereby saving up to 40% on wood material.